Manipulating the Torsion of Molecules by Strong Laser Pulses - Madsen, C. B.; Madsen, L. B.; Viftrup, S. S.; Johansson, M. P.; Poulsen, T. B.; Holmegaard, L.; Kumarappan, V.; Jørgensen, K. A.; Stapelfeldt, H. (My University, 2009)
We demonstrate that strong laser pulses can induce torsional motion in a molecule consisting of a pair of phenyl rings. A nanosecond laser pulse spatially aligns the carbon-carbon bond axis, connecting the two phenyl rings, allowing a perpendicularly polarized, intense femtosecond pulse to initiate torsional motion accompanied by an overall rotation about the fixed axis. We monitor the induced motion by femtosecond time-resolved Coulomb explosion imaging. Our theoretical analysis accounts for and generalizes the experimental findings.